BIMBINGAN MENTAL SPIRITUAL DALAM MENUMBUHKAN SELF-CONFIDENCE BAGI PENYANDANG EKS-PSIKOTIK - Siti Kris Fitriana Wahyu Lestari (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
This research aims to describe mental-spiritual guidance in fostering self-confidence for ex-psychotic people, by using the research library in finding sources relevant to research, and using content analysis as a technique in analyzing existing sources, so as to produce the right conclusion. The results of this study say; in carrying out mental spiritual guidance must use the existing guidelines and provisions, in order to foster self-confidence for people with ex psychotics.